MODEL PEMBACAAN KRITIS TEKS-TEKS KEISLAMAN KAUM FEMINIS - Muhandis Azzuhri (MUWAZAH : jurnal kajian gender, 2014)
Study feminism can not be separated from theological studies. Almost all religions have bad treatments against women. The position of women in some religions are placed as "The Second Sex" and that religion perceives something usually considered "as it should be" (what exactly), instead of "as it is" (whatever they are). Riffat Hassan and Amina Wadud form of interpreting the verses of the Qur'an which is far from the spirit of liberation theology with a feminine approach. Feminism is understood as the liberation of all the oppression of humanity.